Impact of supplementation with beetroot juice (Beta vulgaris L) on levels of malondialdehyde and antioxidant status in athletes - Fajar Apollo Sinaga; Rika Nailuvar Sinaga (Pharmaciana, 2020)
Strenuous physical activity can increase lipid peroxidation, which is characterized by increased levels of malondialdehyde (MDA) and decreased levels of antioxidants. It can drop the athlete's performance and health. It is possible to avoid or reduce lipid peroxidation through supplementation with antioxidants. Beetroot (Beta vulgaris L) produces different forms of natural antioxidants; however, its effectiveness still needs to be investigated. This research aimed to determine the impact of beetroot juice on the malondialdehyde concentration and antioxidant status during strenuous physical activity. The research used experimental (pre-test-post-test) using a control group. The researchers divided a total of 30 students who met the criteria into two groups (Experiment; n = 15; control; n = 15). The experimental group drank 250 mL of the juice 1 hour before training for four weeks. After the strenuous physical activity was carried out with a beep test, the researchers also checked the concentrations of MDA, TAC, and VO2max. The findings indicated a decrease in MDA concentration and an increase in TAC and VO2max to the training group that received 250 ml beet juice (p <0.05). The research concluded that beetroot juice administration during exercise could reduce malondialdehyde concentration and increase total antioxidant capacity and VO2max in athletes.